The orientalising phenomenon on Crete, 9th-7th centuries BC - Diener, AS (2016)
This thesis compiles and assesses orientalising artefacts from EIA Crete, which by definition are those that emulate Near Eastern models in design, style or technique. While oriental imports discovered on Crete have been the subject of several recent publications, there are currently no studies that deal with orientalising finds from the island in a similarly comprehensive manner. The aim of the present work is to fill this gap in scholarship and to provide a solid basis for interpretation. Following a multifaceted approach, the thesis offers an in-depth investigation of relevant pottery, terracottas, sculpture and metal finds. These classes of objects are investigated in terms of types, contexts and iconographies; they are then compared to potential Near Eastern models, which are examined in equal detail where appropriate. Based on this evidence, presumed connections to the Near East are challenged or substantiated while novel links are added, offering fresh insights into the meaning of the Cretan material. A critical revaluation of Cretan contacts with the Near East puts gained findings into a larger perspective of socio-political relations. The final part of the thesis suggests a new interpretation of the material, stressing the importance of Cretan agency, cultural self-definition and the multivalent nature of the orientalising phenomenon on the island.